The Rate Capability Limitation in High-Energy-Density Lithium-Ion Batteries: Origins and Mitigation Strategies - Wu, Chenming (Transactions on Environment, Energy and Earth Sciences, 2026)
In the development of electric vehicles, the advancement of batteries is undoubtedly the most crucial aspect. There are two key indicators that are particularly important for the use of batteries, namely energy density and charging rate. They correspond respectively to the driving range of electric vehicles and the charging time. An excellent battery must possess both high energy density and high charging rate. However, electrode materials that provide high energy density (such as high-nickel positive electrodes and silicon-based negative electrodes) often come with poor rate performance and cycle stability. This leads to problems such as high temperatures during charging or short battery lifespan. This paper systematically analyzes the limiting mechanisms of each component of the battery (with a focus on the positive and negative electrodes) on rate performance, and reviews the latest material-level and system-level improvement strategies. Finally, it summarizes the advantages and disadvantages of existing technologies and looks forward to possible future research directions.
Keywords: Lithium-ion battery; high energy density; fast charging; electrode material; interface dynamics.